Vascular ATP-sensitive potassium channels impact spatial and temporal oxygen transport: implications for sulphonylurea therapy - Holdsworth, Clark Thomas (Kansas State University, 2015)
Matching local muscle O[subscript]2-supply to O[subscript]2-demand during the prodigious exercise-induced metabolic challenge is achieved through coordinated mechanisms of vascular control. The unique sensitivity of ATP-sensitive potassium (K[subscript]ATP) channels to cell metabolism indicates the potential to match energetic demand to peripheral O[subscript]2 transport. The aim of this dissertation was to determine the magnitude and kinetics of the K[subscript]ATP channel contribution to vascular control during exercise in health and heart failure. It was hypothesized that K[subscript]ATP channel inhibition via glibenclamide would, in healthy rats, 1) reduce exercising skeletal muscle blood flow and vascular conductance 2) speed the fall of microvascular O[subscript]2 driving pressure (PO[subscript]2mv; set by the O[subscript]2 delivery-O[subscript]2 utilization ratio) during muscle contractions and 3) in heart failure rats, augment the PO[subscript]2mv undershoot and delay the time to reach the contracting steady-state. A total of 55 male Sprague-Dawley rats were used under control and glibenclamide conditions (5 mg kg[superscript]-1). Hindlimb muscle blood flow (radiolabelled microspheres) was determined at rest (n = 6) or during treadmill exercise (n = 6-8; 20, 40 and 60 m min[superscript]-1, 5% incline). Spinotrapezius muscle PO[subscript]2mv (phosphorescence quenching) was measured in 16 heart failure (coronary artery ligation) and 12 healthy rats and during 180 s of 1-Hz twitch contractions (~6 V). The major effects of glibenclamide were, in healthy rats, 1) a reduction in exercising hindlimb skeletal muscle blood flow with the greatest effect in predominantly oxidative muscle fiber types and at higher running speeds 2) an increased prevalence of the undershoot of PO[subscript]2mv steady-state and doubled time to reach the steady-state and 3) in heart failure rats, a reduced baseline PO[subscript]2mv, an augmented undershoot of the steady-state and time to reach steady-state and a reduction in the mean PO[subscript]2mv during contractions. These data suggest that the K[subscript]ATP channel contributes substantially to exercise-induced hyperemia and may contribute to the slowing of VO[subscript]2 kinetics given the spatial and temporal effects of glibenclamide. The K[subscript]ATP channel-mediated protection against a severe O[subscript]2-delivery to O[subscript]2-utilization mismatch at the onset of contractions raises serious concerns for sulphonylurea treatment in diabetes which is likely to cause perturbations of [metabolite] and compromise exercise tolerance.
Keywords: Vascular control; Microcirculation; Exercise; Heart failure; Skeletal muscle; Vasodilation; Kinesiology (0575); Pharmacology (0419); Physiology (0719)